Homoeostatic maintenance of nonstructural carbohydrates during the 2015–2016 El Niño drought across a tropical forest precipitation gradient. (7th January 2019) - Dickman, Lee Turin; McDowell, Nate G.; Grossiord, Charlotte; Collins, Adam D.; Wolfe, Brett T.; Detto, Matteo; Wright, S. Joseph; Medina‐Vega, José A.; Goodsman, Devin; Rogers, Alistair; Serbin, Shawn P.; Wu, Jin; et al.
Abstract: Nonstructural carbohydrates (NSCs) are essential for maintenance of plant metabolism and may be sensitive to short‐ and long‐term climatic variation. NSC variation in moist tropical forests has rarely been studied, so regulation of NSCs in these systems is poorly understood. We measured foliar and branch NSC content in 23 tree species at three sites located across a large precipitation gradient in Panama during the 2015–2016 El Niño to examine how short‐ and long‐term climatic variation impact carbohydrate dynamics. There was no significant difference in total NSCs as the drought progressed (leaf P = 0.32, branch P = 0.30) nor across the rainfall gradient (leaf P = 0.91, branch P = 0.96). Foliar soluble sugars decreased while starch increased over the duration of the dry period, suggesting greater partitioning of NSCs to storage than metabolism or transport as drought progressed. There was a large variation across species at all sites, but total foliar NSCs were positively correlated with leaf mass per area, whereas branch sugars were positively related to leaf temperature and negatively correlated with daily photosynthesis and wood density. The NSC homoeostasis across a wide range of conditions suggests that NSCs are an allocation priority in moist tropical forests. Abstract : Nonstructural carbohydrates (NSCs), the organic compounds that drive plant metabolism, have rarely been studied in moist tropical forests, so their regulation in these systems is poorly understood. We measured foliar and branch NSCs in canopy trees across a large precipitation gradient in Panama during the 2015–2016 El Niño to examine how short‐ and long‐term climatic variation impact carbohydrate dynamics. There was a large variation in NSCs across species; however, there was no change in total NSCs as the drought progressed nor across the rainfall gradient, suggesting that NSCs are an allocation priority in moist tropical forests.